Performance analysis of MAC protocol for cooperative MIMO transmissions in WSN - Ahmad, Mohd Riduan; Dutkiewicz, Eryk; Huang, Xiaojing (2008)
Cooperative Multi-In Multi-Out (MIMO) schemes can reduce both transmission energy and latency in distributed wireless sensor networks (WSNs). When circuit energy is considered in such networks, the total energy consumed as the number of cooperating nodes increases becomes of particular interest. In addition, most of the previous works focused only on space-time-block-code (STBC) schemes and ignore other MIMO schemes. In this paper we present a comparison study of three cooperative MIMO schemes: beamforming (BF), STBC and spatial multiplexing (SM) where both the transmission and circuit energies are considered. We consider a wireless sensor network operating in quasi-static Rayleigh fading channels with M cooperating transmit nodes and N cooperating receive nodes. We show that the single-in-single-out (SISO) scheme is more energy-efficient and has lower packet latency at higher regions of transmission power while the three cooperative MIMO schemes are more energy-efficient and outperform the SISO scheme at the lower regions. From our analysis, we can conclude that, beamforming outperforms both the SM and STBC schemes in term of energy-efficiency and lower packet latency. Also we suggest that the beamforming scheme utilising two transmit nodes results in an efficient cooperative system.